2015
DOI: 10.1016/j.devcel.2015.03.025
|View full text |Cite
|
Sign up to set email alerts
|

How Actin Initiates the Motor Activity of Myosin

Abstract: SUMMARY Fundamental to cellular processes are directional movements driven by molecular motors. A common theme for these and other molecular machines driven by ATP is that controlled release of hydrolysis products is essential to use the chemical energy efficiently. Mechanochemical transduction by myosin motors on actin is coupled to unknown structural changes that result in the sequential release of inorganic phosphate (Pi) and MgADP. We present here a myosin structure possessing an actin-binding interface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
344
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(386 citation statements)
references
References 53 publications
36
344
5
1
Order By: Relevance
“…The full powerstroke extrapolated from the myosin V PPS structure that we crystallized is also comparable (27 vs. 25 nm) to what has been measured (18). It is possible that our slightly larger extrapolated swing is attributable to the initial movement that is produced in the transition from the PPS to the phosphate release state on actin (P i R state), which we have proposed forms the initial stereospecific interface with actin and thus represents the true beginning of the powerstroke (29). Note that the PPS cannot be the true beginning of the powerstroke on actin, because its interaction is weak, nonstereo-specific and likely not well-constrained.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The full powerstroke extrapolated from the myosin V PPS structure that we crystallized is also comparable (27 vs. 25 nm) to what has been measured (18). It is possible that our slightly larger extrapolated swing is attributable to the initial movement that is produced in the transition from the PPS to the phosphate release state on actin (P i R state), which we have proposed forms the initial stereospecific interface with actin and thus represents the true beginning of the powerstroke (29). Note that the PPS cannot be the true beginning of the powerstroke on actin, because its interaction is weak, nonstereo-specific and likely not well-constrained.…”
Section: Discussionmentioning
confidence: 48%
“…However, we have recently suggested that the true powerstroke on actin is initiated when a different conformation of the motor domain, which we refer as the phosphate release (P i R) state (29), forms following the rearrangement of the PPS upon actin binding. It appears that this rearrangement may involve a small movement of the lever arm.…”
Section: Resultsmentioning
confidence: 99%
“…Only in combination with other findings, like length-step-induced rapid force recovery and low duty ratio at v max , a rate-limiting P i -release preceding a fast force-generating step (model version 5) is the most consistent sequential model. Recently, a novel crystal structure of myosin was found that possesses a fully formed actin interface and opened a backdoor for P irelease with minimal rotation of the lever arm (20). This structure implies that the P i -release can occur before the power stroke, different from kinetic analysis of P i liberated from myosin and structural changes by FRET that indicate the power stroke can occur before P i -release (38).…”
Section: Synthesismentioning
confidence: 99%
“…Analysis of force transients induced by photolytic release of caged-P i led to the perception that the first force-generating step is an isomerization of an ADP.P i -binding state that precedes the P i -release (13,14,16). However, other models and recent evidence from novel crystal structures support a more direct coupling of the first force-generating step to P i -release (3,(18)(19)(20). Furthermore, force transients induced by length steps were often interpreted in terms of this force-generating step occurring independently or after P i -release (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that loop-2 of myosin initiates weak binding of myosin to the TF (21,22). Subsequent binding of the lower L50 domain of myosin to F-actin through the helix-turn-helix motif (23) promotes P i release (24) and completes the initial strong binding of myosin to F-actin. We approximated the initial strong binding mode of myosin using the same approach described by von der Ecken et al (23) (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%